Clozapine is associated with secondary antibody deficiency. (12th February 2019) - Ponsford, Mark; Castle, Daniel; Tahir, Tayyeb; Robinson, Rebecca; Wade, Wendy; Steven, Rachael; Bramhall, Kathryn; Moody, Mo; Carne, Emily; Ford, Catherine; Farewell, Daniel; Williams, Paul; et al.
Abstract : Background: Schizophrenia affects 1% of the population. Clozapine is the only medication licensed for treatment-resistant schizophrenia and is intensively monitored to prevent harm from neutropenia. Clozapine is also associated with increased risk of pneumonia although the mechanism is poorly understood. Aims: To investigate the potential association between clozapine and antibody deficiency. Methods: Patients taking clozapine and patients who were clozapine-naive and receiving alternative antipsychotics were recruited and completed a lifestyle, medication and infection-burden questionnaire. Serum total immunoglobulins (immunoglobulin (Ig)G, IgA, IgM) and specific IgG antibodies to haemophilus influenzae type B, tetanus and IgG, IgA and IgM to pneumococcus were measured. Results: Immunoglobulins were all significantly reduced in the clozapine-treated group ( n = 123) compared with the clozapine-naive group ( n = 111). Odds ratios (ORs) for a reduction in clozapine:control immunoglobulin values below the fifth percentile were IgG, OR = 6.00 (95% CI 1.31–27.44); IgA, OR = 16.75 (95% CI 2.18–128.60); and IgM, OR = 3.26 (95% CI 1.75–6.08). These findings remained significant despite exclusion of other potential causes of hypogammaglobulinaemia. In addition, duration on clozapine was associated with decline in IgG. A higher proportion of the clozapine-treated group reported taking more than five courses of antibiotics in the preceding year (5.3% ( n = 5) versus 1% ( n = 1). Conclusions: Clozapine use was associated with significantly reduced immunoglobulin levels and an increased proportion of patients using more than five antibiotic courses in a year. Antibody testing is not included in existing clozapine monitoring programmes but may represent a mechanistic explanation and modifiable risk factor for the increased rates of pneumonia and sepsis-related mortality previously reported in this vulnerable cohort. Declaration of interest: S.J. has received support from CSL Behring, Shire, LFB, Biotest, Binding Site, Sanofi, GSK, UCB Pharma, Grifols, BPL SOBI, Weatherden, Zarodex and Octapharma for projects, advisory boards, meetings, studies, speaker and clinical trials.